Water districts shocked at state's sudden shift - Fitchette, Todd (Southwest Farm Press, 2021)
California will no longer negotiate with several water districts over the so-called voluntary agreements that all along were viewed as a veiled attempt to take water that does not belong to the state and force farmers to fix water quality problems allowed by the state. The letter continues by claiming future voluntary agreements "will be subject to third-party peer review and environmental analysis pursuant to the Water Code and the California Environmental Quality Act." Turlock and Modesto irrigation districts are suing the state over its decision to move forward with "implementation of their flawed Phase 1 Bay-Delta Water Quality Control Plan."